Sex Differentials in Unemployment Rates: A Case for No Concern - Johnson, Janet L. (Journal of Political Economy, 1983)
This paper reevaluates the concept of unemployment in the context of differing labor market and nonmarket opportunities for men and women, discussing common fallacies in female to male unemployment rate comparisons and their use as an indicator of labor market equality. Suggestive empirical evidence is presented for an alternative unemployment rate concept for women, for interpreting the procyclical variation in female to male unemployment rate differentials, and for decomposing unemployment differences into differences in labor market characteristics and in behavioral coefficients for the two sexes. The paper concludes that a large part of the observed unemployment rate differential may be attributed to the definition and methodology used in deriving unemployment statistics rather than to discrimination in productive opportunities.